Directive Speech Act Analysis in I Still Believe Movie’s Utterances - Yudha, Ni Ketut Sekar Sari Anggreni (The Art of Teaching English as a Foreign Language (TATEFL), 2022)
In order to understand about speech act, there is a need to find a good source in finding speech act. Movie is a good source in finding speech act because movie provides many utterances produced by movie’s characters that represents various speech acts. Moreover, this research intends to find out the directives speech act found in the utterances spoken by the two main characters of I Still Believe movie. Furthermore, the result of this research shows that there are 36 directives speech act found, and those utterances considered as directives speech act are in the form of invitation, order, and request. Therefore, the functions of the utterances considered as directives speech act in this research are to invite, to order, and to request. For any further research, other researchers may conduct similar research about speech act in movie but the focus can vary on other type of speech act.